The Effect of Motive on Public Perceptions of the Seriousness of Murder in Israel - Herzog, Sergio (The British journal of criminology, 2004)
Previous research has consistently shown that the public considers murder to be the most serious of criminal offences and that it evaluates the seriousness of such cases on the basis of criminal intent. These findings are widely reflected in formal criminal codes and, therefore, provide support for the consensus model of the criminal law. Pursuant to the consensus-conflict controversy, the aim of this study was to examine whether lack of formal recognition of motive in assessing the seriousness of murders in most criminal codes also reflects the public will. Using a factorial-survey approach, a national sample of the Israeli population evaluated the seriousness of hypothetical murder scenarios, varying randomly with regard to their main characteristics, including underlying motive. As expected, criminal intent significantly affected public perceptions, hence supporting the consensus perspective. However, some homicide motives, such as prolonged domestic abuse and mercy considerations, also had a significant effect. The implications of the findings are discussed